The green entrepreneurial boom: how China’s low-carbon policies are reshaping urban economies - Zhu, Honggen; Xi, Wei (Frontiers in Environmental Science, 2025)
Low-carbon policies represent a crucial initiative and primary pathway for China’s low-carbon transition, holding significant importance for green economic development. Building upon an analysis of the implementation context of low-carbon policies, this study employs a two-way fixed effects model to empirically evaluate the impact of these policies on urban green entrepreneurship using Chinese city panel data from 2007 to 2022. It further examines the mechanisms through which low-carbon policies influence urban green entrepreneurship. Results indicate that low-carbon policies exert a significant positive impact on urban green entrepreneurship, promoting it through both green innovation incentives and green consumption drivers. Across geographically distinct cities, these policies show a weaker effect on green entrepreneurship in Northwest China compared to Southeast China. Among cities with varying characteristics, the policy’s boost to green entrepreneurship is more pronounced in cities with lower financial development levels. Therefore, China should further promote low-carbon policies, actively explore personalized green development models tailored to urban characteristics, optimize the policy environment for low-carbon industries, and enhance green innovation mechanisms. Concurrently, it should vigorously promote green development concepts, guide public green consumption, and foster urban green entrepreneurship.